2017
DOI: 10.5632/jila.80.719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Observer’s Impressions of Roost Containing Behavior of the Barn Swallow (<i>Hirundo rustica</i>) in Kanagawa Prefecture

Abstract: The objective of this study was to evaluate observer's impressions of roost containing behavior and to assess the effectiveness of awareness efforts regarding the conservation of the barn swallow (Hirundo rustica), which is endangered in Japan. In Kanagawa Prefecture retarding park, a group of observers habitually meets to observe the roost containing of the barn swallow, and a questionnaire was administered to 97 participants recruited from this group. Analysis using the semantic differential method revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Epidemiology : Cryptosporidiosis in cattle in Japan was first reported in calves from Okayama, Miyagi, and Hokkaido prefectures [ 15 , 61 , 135 , 139 , 179 ] according to Kaneta and Nakai [ 71 ]. Earlier studies showed that C. muris or C. muris -like oocysts were present in cattle from Japanese slaughterhouses [ 82 , 118 ] at infection rates of 4.7% in Miyagi [ 122 ], 3.9% in Kanagawa [ 79 ], 2.8% in Shizuoka [ 153 ], 1.2% in Fukushima [ 108 ], 1.2% in Saitama [ 119 ], and 3.4% in Tokushima Prefecture [ 156 ]. The aforementioned studies were mainly published locally and active surveillance was conducted after the year 2000.…”
Section: Reported Animal Cases Of Cryptosporidiosis Species Diversitmentioning
confidence: 99%
“…Epidemiology : Cryptosporidiosis in cattle in Japan was first reported in calves from Okayama, Miyagi, and Hokkaido prefectures [ 15 , 61 , 135 , 139 , 179 ] according to Kaneta and Nakai [ 71 ]. Earlier studies showed that C. muris or C. muris -like oocysts were present in cattle from Japanese slaughterhouses [ 82 , 118 ] at infection rates of 4.7% in Miyagi [ 122 ], 3.9% in Kanagawa [ 79 ], 2.8% in Shizuoka [ 153 ], 1.2% in Fukushima [ 108 ], 1.2% in Saitama [ 119 ], and 3.4% in Tokushima Prefecture [ 156 ]. The aforementioned studies were mainly published locally and active surveillance was conducted after the year 2000.…”
Section: Reported Animal Cases Of Cryptosporidiosis Species Diversitmentioning
confidence: 99%